Pelaksanaan Perjanjian Pembiayaan Usaha Mikro, Kecil, Dan Menengah (UMKM) Pada PT. Permodalan Nasional Madani Mekaar (PERSERO) (Studi Masyarakat Kelurahan Yosomulyo Kota Metro) - Primadi, Lingga; Kasmawati, Kasmawati; Ramadhan, Harsa Wahyu; Zazili, Ahmad; Mustika, Dora (Universitas Pahlawan Tuanku Tambusai, 2025)
The aim of this research is first, to analyze the legal relationship in the implementation of loan and borrowing agreements at the Madani Mekaar National Capital (Persero) in the Yosomulyo sub-district, Metro City; secondly, to analyze the obstacles that occur in the implementation of lending and borrowing at PNM Mekaar (Persero) in Yosomulyo Metro City. This type of research is normative-empirical legal research with descriptive legal research type. The research problem approach is nonjudicial case study. Research data sources are primary and secondary data. Data collection methods were carried out by means of literature study, document study and interviews. Data processing methods are data inspection, data marking, data reconstruction, data systematization. The data was analyzed qualitatively. The research results show that the legal relationship between PT PNM Mekaar (Persero) and customers in Yosomulyo Village is a reciprocal contractual relationship, where both parties have rights and obligations that are clearly regulated in the business financing agreement. Implementation of financing loans at PT. PNM Mekaar (Persero) goes through four stages, namely fulfilling application requirements, surveying, implementing financing, and implementing rights and obligations. Then there are obstacles in implementing business financing agreements, namely default in implementing financing agreements at PT PNM Mekaar (Persero), in the form of delays in installment payments and customers running away, thus disrupting the smooth running of financing. Factors causing default include unstable financial conditions of customers and use of funds that are not fit for purpose.